Endovascular Management of Secondary Aortoduodenal Fistula: The Importance of Gut Restoration - Moulakakis, Konstantinos G.; Kakisis, John; Dalainas, Ilias; Smyrniotis, Vasilis; Liapis, Christos D. (International Journal of Angiology, 2015)
Secondary aortoenteric fistula (SAEF) is a rare, life-threatening complication of aortic reconstructive surgery. Graft excision associated with gut repair and extra-anatomic bypass or in situ aortic reconstruction is the best option. However, it is associated with high mortality rates, especially when undertaken in unstable patients with severe comorbidities. We present a case of SAEF successfully treated by endovascular repair and gut restoration. After laparotomy, a dense inflammatory “frozen” mass was found around the involved part of the duodenum and the aortic sac. Because of his comorbidities, the difficulty in dissection of the aortic sac and the risk of damage in adjacent organs, the initial plan for aortic reconstruction was abandoned. A surgical isolation of the third portion of the duodenum and a duodenum–jejunal anastomosis were performed. An Endurant endograft 32–16–16 mm (Medtronic, Inc., Minneapolis, MN) was implanted to achieve aortic continuity. Twenty months postdischarge, the patient remains in good general condition, afebrile, and with normal laboratory tests and inflammation markers. In high-risk patients, endovascular intervention combined with gut repair without further aortic reconstruction can be a permanent solution requiring, however, close surveillance.
Keywords: secondary; aortoenteric fistula; endovascular; gut repair